2017
DOI: 10.1039/c7lc00184c
|View full text |Cite
|
Sign up to set email alerts
|

3D measurement and simulation of surface acoustic wave driven fluid motion: a comparison

Abstract: The characterisation of the fluid motion induced by the acoustic streaming effect is of paramount interest for novel microfluidic devices based on surface acoustic waves (SAWs), e.g. for a detailed description of the achievable mixing efficiency and thus the design of such devices. Here, we present for the first time a quantitative 3D comparison between experimental measurements and numerical simulations of the acoustic streaming induced fluid flow inside a microchannel originating from a SAW. On the one hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…The experimental results suggested that the uid streams rotated in the clockwise direction within the microchannel cross-section which is consistent with the direction of the acoustic streaming ow eld produced by a SAW. 39 As the uid streams owed from the b 2 -b 2 0 to the b 3 -b 3 0 congurations, the IPA and FC-40 streams owed into the le and right ow paths, respectively. The two uid streams were completely altered and clearly separated from one another.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results suggested that the uid streams rotated in the clockwise direction within the microchannel cross-section which is consistent with the direction of the acoustic streaming ow eld produced by a SAW. 39 As the uid streams owed from the b 2 -b 2 0 to the b 3 -b 3 0 congurations, the IPA and FC-40 streams owed into the le and right ow paths, respectively. The two uid streams were completely altered and clearly separated from one another.…”
Section: Resultsmentioning
confidence: 99%
“…Here we take into consideration the whole volume of the fluid, including microstructures (such as an anechoic corner, shown in Fig 1 A), enabling us to build an accurate description of an acoustically pumped microfluidic system. 15 We do not consider the reflections off the walls of the microchannels (which are most often made of elastomeric materials with a low acoustic impedance, and which do not generate significant reflections). It is important to note that, where other materials are used in the construction of the microfluidic network (such as glass or silicon for example), the contribution of such reflections will be significant and will need to be considered systematically.…”
Section: Acoustic Fields In Fluids Due To Rayleigh Acoustic Wavesmentioning
confidence: 99%
“…When a channel is smaller than the attenuation length of the SAW, the magnitude of streaming flows is significantly decreased. Recent advances have taken the so-called 'anechoic corner' into account and shown good agreement between simulation and experiment, 15,16 but only over a limited range of frequencies, preventing the generation of significant insight into the interplay between acoustic frequency and streaming efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, this is 3D-simulation. 50,51 In principle, the 3D scattering problem can also be solved using FEM and PML but not on ordinary personal computers.…”
Section: Introductionmentioning
confidence: 99%